Assessing levels of endangerment in the Catalogue of Endangered Languages (ELCat) using the Language Endangerment Index (LEI). - Lee, Nala Huiying; Van Way, John (Language in Society, 2016)
The Catalogue of Endangered Languages (ELCat) is the central feature of the Google-powered Endangered Languages Project (endangeredlanguages.com), which is a venue for sharing information and resources on the world's endangered languages and the knowledge contained in them. One key feature of ELCat is a quantitative measure that can be used to understand the level of endangerment of any language. Quantitative measurements are needed to compare language vitality across a variety of contexts around the globe, and can be used as a parallel to measurements of other forms of threats to biocultural diversity. This article addresses the development of the Language Endangerment Index (LEI). Based on four factors (intergenerational transmission, absolute number of speakers, speaker number trends, and domains of use), this index is different from other methods of assessment in several ways, especially as it can be used even if limited information is available. (Language endangerment, vitality, intergenerational transmission, speaker numbers, domains of language use)*